Evaluation of the Corrosion Resistance of Carbons for Use as PEM Fuel Cell Cathode Supports. Issue 12 (1st January 2015) - Forouzandeh, Farisa; Li, Xiaoan; Banham, Dustin W.; Feng, Fangxia; Ye, Siyu; Birss, Viola
Abstract : The electrochemical corrosion of the carbon-based catalyst support materials used in proton exchange membrane fuel cells (PEMFCs), especially at the cathode, has a significant impact on PEMFC lifetime. Thus, an effective and reliable method for the evaluation of the corrosion resistance of new carbon supports, as they are developed, is required. In the present work, a novel approach that allows for the ranking of carbon supports for their corrosion susceptibility has been developed, based on the testing of a conventional microporous carbon material (Vulcan carbon, VC) and two ordered mesoporous carbons (OMCs), synthesized using sucrose and anthracene as the carbon precursors. While cyclic voltammetry does reveal important information about surface area and surface oxidation changes, the charge passed during potential stepping between 0.8 and 1.4 V vs. RHE was found to be still more informative, with the cathodic charge used to continuously correct for the changing surface area of the carbon during its oxidation. Based on this approach, it was found that VC, which is the more crystalline material, is more stable to oxidation than the OMCs, as expected, while the anthracene precursor leads to a more stable OMC than when sucrose is used.